THE IMPORTANCE OF ECONOMIC, CULTURAL, AND SOCIAL FORECASTING IN UZBEKISTAN - Nasiba Normuminova (Bright Mind Publishing, 2025)
This article examines the role of forecasting in economic development, cultural heritage preservation, and ensuring social stability. From an economic perspective, forecasting helps Uzbekistan utilize resources efficiently, attract investments, and identify new market opportunities. In turn, this stimulates economic growth and creates job opportunities. From a cultural perspective, forecasting plays a crucial role in preserving and developing Uzbekistan’s rich cultural heritage. This process facilitates the planning of cultural events, the development of tourism, and the strengthening of international cooperation.
Keywords: Economic development, efficient resource utilization, investments, market opportunities, job creation, cultural heritage, tourism development, international cooperation, social stability, public needs, social programs, promoting equality, strategic planning, sustainable development.